B-cell depletion attenuates serological biomarkers of fibrosis and myofibroblast activation in IgG4-related disease. Issue 12 (20th August 2014) - Della-Torre, Emanuel; Feeney, Eoin; Deshpande, Vikram; Mattoo, Hamid; Mahajan, Vinay; Kulikova, Maria; Wallace, Zachary S; Carruthers, Mollie; Chung, Raymond T; Pillai, Shiv; Stone, John H
Abstract : Objectives: Fibrosis is a predominant feature of IgG4-related disease (IgG4-RD). B-cell depletion induces a prompt clinical and immunological response in patients with IgG4-RD, but the effects of this intervention on fibrosis in IgG4-RD are unknown. We used the enhanced liver fibrosis (ELF) score to address the impact of rituximab on fibroblast activation. The ELF score is an algorithm based on serum concentrations of procollagen-III aminoterminal propeptide, tissue inhibitor of matrix metalloproteinase-1 and hyaluronic acid. Methods: Ten patients with active, untreated IgG4-RD were enrolled. ELF scores were measured and correlated with the IgG4-RD Responder Index, serum IgG4, circulating plasmablasts and imaging studies. Through immunohistochemical stains for CD3, CD20, IgG4 and α-smooth muscle actin, we assessed the extent of the lymphoplasmacytic infiltration and the degree of fibroblast activation in one patient with tissue biopsies before and after rituximab. Results: The ELF score was increased in patients with IgG4-RD compared with healthy controls (8.3±1.4 vs 6.2±0.9; p=0.002) and correlated with the number of organs involved (R 2 =0.41; p=0.04). Rituximab induced significant reductions in the ELF score, the number of circulating plasmablasts and the IgG4-RD Responder Index (p<0.05 for all three parameters). Rituximab reduced both the lymphoplasmacytic infiltrate and myofibroblast activation. IgG4-RD relapse coincided with recurrent increases in the ELF score, indicating reactivation of collagen deposition. Conclusions: The ELF score may be a clinically useful indicator of active fibrosis and the extent of disease in IgG4-RD. B-cell depletion has the potential to halt continued collagen deposition by attenuating the secretory phenotype of myofibroblasts in IgG4-RD lesions.